Planning and implementing a structured literature search strategy in biomedicine - David Ožura (Institute of Oncology Ljubljana, 2021)
A review article is an article in which the latest published works in a certain scientific field or the work of an individual researcher or research group are discussed, summarized, analysed, evaluated and synthesized. The preparation of reviews is complex, extensive and time-consuming. Due to this complexity, several people with different knowledge usually participate, and a librarian is also involved in the role of information specialist. The search process consists of the following steps: plan the review and document the search process, determine a clear and focused question, develop inclusion and exclusion criteria, carry out early scoping searches, identify the specific bibliographic databases, identify key search terms, identify appropriate subject headings (index terms), synonyms and free text words, use Boolean operators, parentheses and database-appropriate field codes, optimize the search, translate the search for other databases, screen titles and abstracts, obtain full-text papers, screen the full-text papers. As an example in practice, we will choose the planning and implementation of an inquiry in the field of oncology, which will determine the possible link between tobacco smoking and cervical cancer.